An innovative way for the delignification of Phragmites australis residues by steam explosion and γ‐valerolactone microwave assisted extraction. Issue 3 (17th March 2017) - Cavalaglio, Gianluca; Cotana, Franco; Gelosia, Mattia; Pompili, Enrico; D'Antonio, Silvia; Ingles, David
Abstract : This work aimed at optimizing the conditions for lignin removal in Phragmites australis processing residues from the manufacturing of local handicrafts. The delignification consisted of a double step treatment. The first step was represented by steam explosion (SE) pretreatment for the deconstruction of the lignocellulosic matrix and solubilization of the hemicelluloses to enhance the subsequent lignin extraction. The second step consisted in the organosolv extraction of lignin from the steam‐pretreated P. australis by microwave assisted extraction (MAE) using green solvent γ‐valerolactone. The optimization was carried out using design of experiments and response surface methodology generating a central composite design. The investigated factors were the severity factor (log R0 ) for the SE pretreatment and time and temperature for the MAE treatment. The processes led to a cellulose‐rich pulp with a delignification of 75%. © 2017 American Institute of Chemical Engineers Environ Prog, 36: 736–741, 2017